Corporate Social Responsibility in the 21st Century - Sarfraz, Muddassar (Business, Management and Economics, 2023)
Corporate social responsibility (CSR) is a fundamental part of corporate entities to assist human efforts toward addressing global challenges rather than exacerbating them. CSR helps companies to achieve social, economic, and ecological legitimacy. It also shapes industrial practices by maximizing socio-ecological sustainability. This book provides a practical understanding of CSR arrangements and practices. It demonstrates the significance, commitments, challenges, and benefits of CSR in different parts of the world. It includes seventeen chapters that address such topics as sustainability and corporate innovation, CSR in the era of COVID-19, CSR and blockchain technology, CSR in universities, gender diversity in CSR, and much more.